Strategic leaders for the 21st century. - McCausland, Jeffrey D. (Nova Science Pub., 2009)
This book focuses on the human capital required to succeed in the contemporary national security environment. It begins with an examination of the multitude of studies by both government and private agencies concerning this problem over the past 2 decades. It reviews the current development programs in three departments of the Federal Government -- the Department of Defense, Department of State, and Central Intelligence Agency. Finally, the author outlines a proposal for a National Security Professional Program to meet this pressing need.